Preliminary clinical experience with Calypso anchored beacons for tumor tracking in lung SBRT. Issue 9 (25th June 2020) - Sarkar, Vikren; Szegedi, Martin; Paxton, Adam; Nelson, Geoff; Rassiah‐Szegedi, Prema; Reddy, Chakravarthy B.; Tao, Randa; Hitchcock, Ying J.; Kokeny, Kristine E.; Salter, Bill J.
Abstract : Purpose: To present our preliminary experience with the recently released Calypso lung beacons to track lung tumor location during stereotactic body radiation therapy (SBRT). Materials/Methods: Five recent lung SBRT patients had Calypso lung beacons implanted for tumor tracking during treatment. Beacons were placed by a pulmonologist using fluoroscopic navigation within 1 week prior to planning four‐dimensional computed tomography (4DCT) acquisition. Patients were immobilized in a full‐body double‐vacuum bag. For the first three patients, a verification 4DCT was obtained prior to the first fraction with the patient in the treatment position to assess both beacon migration and motion of tumor and beacons relative to planning day. For each treatment fraction, Calypso was used to position the patient. A verification cone‐beam CT (CBCT) confirmed the Calypso‐defined target position was appropriate. Real‐time Calypso tracking information was also acquired and compared to an action level that was used to determine if the tumor migrated outside of the planning target volume. Results: For four patients, the implant procedure was well tolerated, with average CBCT‐based shifts being within 0.2 mm of the shifts reported by Calypso at the time of imaging. The other patient had a small pneumothorax due to very peripheral tumor location and experienced beacon migration. However, the patient quickly recovered from the pneumothorax, and after deactivating that beacon, motion tracking was possible throughout his treatment. Conclusions: All patients were successfully treated with SBRT using the newly released Calypso lung beacons, with initial positioning confirmed by this clinic's current clinical standard of CBCT. The system allowed us to validate, with real‐time confirmation, that the planned internal target volumes were appropriate to each day's extent of actual tumor motion. An efficient and effective workflow for utilizing the new lung beacons for SBRT treatments was developed.